Organisation, Structure and Innovation Performance in Different Environments - Cosh, A; Fu, X; Hughes, A (SpringerLink, 2010)
This paper examines the relationship between organisation structure and innovation performance in a large sample of UK small and mediumsized enterprises. It asks whether there is an optimal structure and whether this differs between different firm environments and between young and older firms. We find that the influences on the ability to innovate differ from those on the commercialisation of innovations. We show that decentralised decisionmaking, supported by a formal structure and written plans, supports the ability to innovate in most circumstances and is superior to other structures. We also find some evidence that young firms operating in high technology sectors with informal structures have a greater tendency to be innovative. In addition, we find very few differences between young and older firms in terms of their optimal structures in low technology sectors.